Prevalence of Positivity for Diabetes-Associated Autoantibodies in Individuals with Type 2 Diabetes and Their Further Characterisation: Cross-sectional Study from Slovakia - Rončáková, M; Davani, Arash; Mikušová, Veronika; Ságová, Ivana; Novodvorský, Peter; Martinka, Emil (Diabetes therapy, 2023)
BACKGROUND: Individuals initially diagnosed with type 2 diabetes (T2D) might exhibit positivity for diabetes-associated autoantibodies (DAA +). We investigated the prevalence of DAA positivity in a group of individuals with T2D who were referred to a tertiary diabetes centre within a pre-specified period of time. We aimed to identify characteristics linked with DAA positivity by comparing DAA + individuals with their DAA-negative counterparts. METHODS: This was a cross-sectional study into which all T2D patients referred to the National Institute of Endocrinology and Diabetology, Ľubochňa, Slovakia, between 1 January and 30 June 2016 were included. Data on > 70 participants' characteristics, including antibodies against glutamic acid decarboxylase (anti-GAD65), insulinoma-associated antigen IA-2 (IA-2A) and insulin (IAA), were collected. RESULTS: Six hundred and ninety-two individuals (387, 55.6% female) with a median (range) age of 62 (24-83) years, HbA1c of 8.9 (5.0-15.7)% [74 (31-148 mmol/mol)] and diabetes duration of 13.0 (0-42) years were analysed. One hundred and forty-five (145/692, 21.0%) tested positive for at least one DAA; 136/692 (19.7%) were positive for anti-GAD65, 21/692 (3.0%) were positive for IA-2A and 9/692 (1.3%) were positive for IAA. Only 84.9% of the DAA + individuals aged > 30 years at the time of diabetes diagnosis met the current diagnostic criteria for latent autoimmune diabetes of adults (LADA). DAA + differed from DAA - individuals in multiple characteristics, including the incidence of hypoglycaemia. CONCLUSION: Several pathological processes linked with distinct types of diabetes can develop in parallel, including insulin resistance and autoimmune insulitis. In this single-centre cross-sectional study from Slovakia, we report a higher than previously published prevalence of DAA positivity in a group of individuals with a formal diagnosis of T2D.